Partner Reading Strategy to Improve Students' Reading Comprehension - Mochlis Ekowijayanto (International Journal of English Education and Linguistics (IJoEEL), 2022)
The researchers decided to implement the Partner Reading Strategy in this research because it is an effective strategy for improving the students' reading comprehension. The students worked together to read, analyze, and discuss the text assigned in this cooperative learning strategy. This research aimed to help the students of the VIII C class of MTs Mambaul Hikam improve their reading comprehension using the Partner Reading Strategy and identify their engagement in learning activities. This research used a Classroom Action Research method as a research design. Partner Reading Strategy is an independent variable, and students' reading comprehension is a dependent variable. The subject of this research were 31 students, consisted of eleven (11) male students and twenty (20) female students. The researchers used some instruments to assess students' reading comprehension: formative tests and summative tests. In collecting the data, the writers used non-tests, including interviews, observation sheets, questionnaires, and field notes. The improvement of students' reading comprehension can be concluded from the improvement of the mean score of pre-test, formative test, and summative test. The summative test was given in the last meeting of each cycle. The result shows that using the Partner Reading Strategy successfully improved students' reading comprehension. Moreover, students' engagement played an influential role and impacted their learning outcomes. Implementing a Partner Reading Strategy can make students be involved in the educational activity and have a high level of engagement to earn high learning outcomes